Ectoparasite fauna of rodents and shrews from four habitats in Kuala Lumpur and the states of Selangor and Negeri Sembilan, Malaysia and its public health significance - Sithambaram, Paramasvaran; Abdullah Sani, Rehana; Hassan, Latiffah; Krishnasamy, M.; Jeffery , J.; Syed Ahmad, Pakeer Oothuman; Salleh, I.; Lim, K. H.; Mohd Ghazali, Sumarni; Louis, Santhana Raj (Malaysian Society of Parasitology and Tropical Medicine, 2009)
A total of 204 rodents comprising 14 host species from four different habitats were examined. Nine rodent species were trapped from the forest and another five species were trapped from the coastal, rice field and urban habitats. Rattus rattus diardii (67%) was the predominant rodent species examined. Fifty six (47.3%) rodents and shrews were found to be infested with at least one of the 20 species of ectoparasite recovered. Mites belonging to the family Trombiculidae were the predominant ectoparasite species recovered. Ticks belonging to the family Ixodidae were recovered mainly from the forest dwelling rodents. Polyplax spinulosa and Hoplopleura pacifica were the common lice species found infesting the urban rodents. Xenopsylla cheopis was the only flea species recovered. The following ecto-parasites have been incriminated as important vectors or as mechanical carriers for the transmission of zoonotic diseases: Ixodes granulatus, Dermacentor sp. Haemaphysalis sp., Amblyomma sp. Ascoschoengastia indica, Leptotrombidium deliense, Ornithonyssus bacoti, Laelaps nuttalli, H. pacifica, P. spinulosa and Xenopsylla cheopis. Urban and forest rodents were significantly higher in ecto-parasitic infestation, compared to rats from the other two habitats. However, there was no significant statistical association between male and female rodents infested with ectoparasites.